Sistem Informasi E-Pet Solution Pada Oranjee Petshop Berbasis Website - Hani Nurhaliza; Yudiastuti, Helda; Rizky Nova Wardani, Kiky; Hadinata, Novri (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Oranjee Petshop is a shop in the city of Palembang that sells pet care products and provides open adoptions for various types of pets. Currently, Oranjee Petshop is not well known to the wider community, the majority of customers are people who live not far from the shop location. This resulted in the store's sales turnover not increasing. The E-Pet Solution Information System is a solution developed to improve operational efficiency and customer service in the pet shop business. Website-based, this system provides easy access for customers to shop, as well as making it easier for employees and owners to manage the business. This research aims to identify the problems faced by pet shops, evaluate the performance of existing systems, and develop better solutions. The method used is the Prototype Method, the aim of this research is to produce a sales website that is more efficient, competitive and customer-oriented.